Fatwa of MUI and Islamic Jurisprudence Council on Stem Cells from The Perspective of Qawaid Fiqhiyyah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Stem Cells are an important topic in contemporary medicine and among contemporary medical fiqh issues that led to scholars differing in the ruling on its treatment as the imams of the madhhab did not previously discuss them. Scholars who allow their use provide strict limitations and provisions for the use of stem cells. Jurisprudential councils around the world took the initiative to issue a decision related to its ruling, including the Indonesian Ulema Council or MUI, and accordingly, they issued a fatwa number 51 of 2020 concerning the use of stem cells. Their fatwa relied on the decision of the Islamic Jurisprudence Council of the Muslim World League in the seventeenth session in 2003. MUI has decided that “Using human stem cells for any purpose is fundamentally haram or forbidden. It is permissible or mubah if there is a legitimate need (hajah shari’yyah).”Meanwhile, the Islamic Jurisprudence Council has initially decided its permissibility if its source is permissible and forbidden if it is among its forbidden sources. Our aim of this research is to advocate for changes in the fatwa that could significantly improve quality of life by ensuring the use of stem cells is available without necessity or hajah shari’yyah. Therefore, we analyzed the ruling of stem cells in both councils from the perspective of qawaid fiqhiyyah related to their fatwa: “The original ruling of beneficial things is permissible.” The study's findings show that among the various decisions issued for the law of stem cells, the Indonesian Ulema Council’s decision contradicts what is best and beneficial for Indonesian society. The council has decided their opinions about the basic use of stem cells, depending on the type of substances in which stem cells are considered.
Keywords: treatment; stem cells; Indonesian Ulema Council; Islamic Fiqh Council